Optimizing Learning Through Gamification in Digital Learning to Improve Physical Education Learning Outcomes - Dos Santos, Hezron Alhim; Dos Santos, Maria Herlinda; Norma Anggara; Endang Pratiwi (Universitas PGRI Palembang, 2024)
Physical Education, Sports, and Health (PJOK) has a crucial role in developing students' physical fitness and motor skills. However, students' motivation in participating in PJOK learning often decreases due to less interesting teaching methods. The gamification approach in digital learning offers innovative solutions to increase student engagement. This study aims to analyze the effectiveness of gamification in digital learning on improving physical education learning outcomes. The method used is classroom action research (CAR) with a quantitative and qualitative approach. The results of the study showed that the implementation of gamification elements, such as point systems, leaderboards, and digital application-based challenges, was able to significantly increase student motivation and learning outcomes. Thus, gamification in digital learning can be an effective strategy to improve the PJOK learning experience.